Late Quaternary glaciation history of monsoon-dominated Dingad basin, central Himalaya, India. (1st February 2018) - Shukla, Tanuj; Mehta, Manish; Jaiswal, Manoj K.; Srivastava, Pradeep; Dobhal, D.P.; Nainwal, H.C.; Singh, Atul K.
Abstract: The study presents the Late Quaternary glaciation history of monsoon-dominated Dokriani Glacier valley, Dingad basin, central Himalaya, India. The basin is tested for the mechanism of landforms preservation in high relief and abundant precipitation regimes of the Higher Himalaya. Field geomorphology and remote sensing data, supported by Optical Stimulated Luminescence (OSL) dating enabled identification of five major glacial events of decreasing magnitude. The oldest glacial stage, Dokriani Glacial Stage I (DGS-I), extended down to ∼8 km (2883 m asl) from present-day snout (3965 m asl) followed by other four glaciations events viz. DGS-II, DGS-III, DGS-IV and DGS-V terminating at ∼3211, 3445, 3648 and ∼3733 m asl respectively. The DGS-I glaciation (∼25–∼22 ka BP) occurred during early Marine Isotope Stage (MIS) −2, characterized as Last Glacial Maximum (LGM) extension of the valley. Similarly, DGS-II stage (∼14–∼11 ka BP) represents the global cool and dry Older Dryas and Younger Dryas event glaciation. The DGS-III glaciation (∼8 ka BP) coincides with early Holocene 8.2 ka cooling event, the DGS-IV glaciations (∼4–3.7 ka BP) corresponds to 4.2 ka cool and drier event, DGS-V (∼2.7–∼1 ka BP) represents the cool and moist late Holocene glacial advancement of the valley. This study suggests that the Dokriani Glacier valley responded to the global lowering of temperature and variable precipitation conditions. This study also highlights the close correlation between the monsoon-dominated valley glaciations and Northern Hemisphere cooling events influenced by North Atlantic climate. Highlights: The study reveals five set of glaciations with decreasing magnitude. Stratigraphically constrained OSL ages suggesting maximum extension of glacier during LGM. Temperature seems to play a major forcing factor for glaciation events. The glacier response of the valley has shown some possible teleconnections with Northern Hemisphere cooling events.